My mom is excellent - Butterworth, Nick. (Cambridge, Mass. : Candlewick Press, 2003)
A young boy describes all the amazing things that his mother can do.
First published: London : Walker, 1989.
1.5.
1.5
K-3
Keywords: Mother and child -- Fiction; Mothers -- Fiction; Mother-child relationship -- Fiction; Mothers -- Fiction